MIBI scintigraphy of parathyroid adenomas: correlation with biochemical and histological markers. (3rd July 2018) - Cordes, Michael; Dworak, Otto; Papadopoulos, Thomas; Coerper, Stephan; Kuwert, Torsten
ABSTRACT: Purpose: In this study, we tested the hypothesis that MIBI-positive and MIBI-negative adenomas of parathyroid glands (APGs) have distinct biochemical and histological markers that could help differentiate MIBI-positive from MIBI-negative APGs.Patients and methods: 40 patients with 41 APGs were included in the study. Patients were enrolled in the study after MIBI scintigraphy examinations had been carried out. Biochemical analyses included serum levels of calcium (Ca), intact parathyroid hormone (iPTH), and 25-hydroxyvitamin D3 (25-OH-D3). All patients had neck ultrasound and MIBI examinations. After surgical resection the APGs were examined histologically.Results: In each of 39 patients one APG could be confirmed by histology, and in one patient, two contralateral APGs were identified. MIBI studies were positive in 73 % and negative in 27 % of the APGs. False-positive cases were not observed. MIBI-negative APGs were only present in patients with iPTH values below 150 pg/ml. In 82 % of MIBI negative studies oxyphilic cells were absent, and this cell type was present in only 18 % of MIBI negative cases (p < 0.001). Regarding cysts within the APGs, no differences were demonstrated between MIBI positive or negative studies (p = 0.32). Fat cells were seen in none of the MIBI -negative studies and in only 3 % of MIBI positive studies (p = 0.08).Conclusions: For APGs, MIBI positivity correlates with serum iPTH concentration. The absence of oxyphilic cells with large numbers of mitochondria in APGs contributes to MIBI negativity, probably because of the reduced binding sites for the radiotracer.